Cidade, Ficção e Memória em Manuel Puig: Um narrador pós-moderno? - Bastiani, Caroline Arenhart de (2014)
This study aims to highlight the Manuel Puig city perspective as well as the imagery of the city design developed by the author throughout his life, based on the study of living space, memory, national identity and city look that have been recorded in their works through interaction with the arts. The Puig novels A Traição de Rita Hayworth (1968), The Buenos Aires Affair (1973) and Cae la Noche Tropical (1988), present different points of view linked to the various stages of his life. The first project, as an example, puts the reader on the mediocrity of the inhabitants of a town in Argentina, whose ideal reference is the capital city Buenos Aires, which aims New York City as a symbol of chimeric city while refusing his hometown, dismissing it. The third work, when dealing with the lives of two Argentine women who are living in Brazil, puts the caller on a breakup of the protagonists with their home country, showing the beauties and privileges of the city of Rio de Janeiro, while denying the city of Buenos Aires. The works were selected as the corpus of study for presenting elements that enable the configuration of the city imaginary showed by Puig: a cinematographic mark, visual arts, music and poetry. The city perspective of the characters evolves in each of the three novels, in relation to the conception of Argentina as the ideal city, changing as the life of the Argentine writer suffers multiple cultural shock upon contact with the reality of many countries and cities that were passed by him due to exile experienced as a result of the Argentine political moment